Allometric scaling of uphill cycling performance - Jobson, S. A.; Woodside, J.; Passfield, L.; Nevill, A. M. (International Journal of Sports Medicine, 2008)
Previous laboratory-based investigations have identified optimal body mass scaling exponents in the range 0.79 - 0.91 for uphill cycling. The purpose of this investigation was to evaluate whether or not these exponents are also valid in a field setting. A proportional allometric model was used to predict the optimal power-to-mass ratios associated with road-based uphill time-trial cycling performance. The optimal power function models predicting mean cycle speed during a 5.3 km, 5.4 % road hill-climb time-trial were (V?O2max · m-1.24)0.55 and (RMPmax · m-1.04)0.54, explained variance being 84.6 % and 70.5 %, respectively. Slightly higher mass exponents were observed when the mass predictor was replaced with the combined mass of cyclist and equipment (mC). Uphill cycling speed was proportional to (V?O2max · mC-1.33)0.57 and (RMPmax · mC-1.10)0.59. The curvilinear exponents, 0.54 - 0.59, identified a relatively strong curvilinear relationship between cycling speed and energy cost, suggesting that air resistance remains influential when cycling up a gradient of 5.4 %. These results provide some support for previously reported uphill cycling mass exponents derived in laboratories. However, the exponents reported here were a little higher than those reported previously, a finding possibly explained by a lack of geometric similarity in this sample.